1989
DOI: 10.1099/0022-1317-70-3-513
|View full text |Cite
|
Sign up to set email alerts
|

The Complete Nucleotide Sequence of Plum Pox Virus RNA

Abstract: SUMMARYThe complete nucleotide sequence of the RNA of an aphid non-transmissible plum pox virus (PPV-NAT) isolate has been determined from five overlapping cDNA clones, cDNA prepared by primer extension was used to determine the 5' terminus. The assembled RNA is 9741 nucleotides in length, excluding a 3' terminal poly(A) sequence. One large open reading frame starts at nucleotide positions 36 to 38 and is terminated with an UAG codon at positions 9522 to 9524. The putative start codon is located at positions 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
143
1
1

Year Published

1990
1990
2002
2002

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(148 citation statements)
references
References 30 publications
3
143
1
1
Order By: Relevance
“…The flexuous particles contain a single-stranded messenger RNA of about 10000 nucleotides with a viral protein covalently linked to the 5' end and a poly(A) tail at the 3' end (for a review see Riechmann et al, 1992). The complete nucleotide sequence of several members of the group is already known (Allison et al, 1986;Domier et al, 1986;Robaglia et al, 1989;Lain et al, 1989;Maiss et al, 1989;Teycheney et al, 1989;Johansen et al, 1991 ; * Author for correspondence. Fax +33 1 30 83 31 95. e-mail robaglia@oxygene.versailles.inra.fr Nicolas & Lalibertr, 1992;Yeh et al, 1992;Jayaram et al, 1992;Vance et al, 1992;Thole et al, 1993;Palkovics et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…The flexuous particles contain a single-stranded messenger RNA of about 10000 nucleotides with a viral protein covalently linked to the 5' end and a poly(A) tail at the 3' end (for a review see Riechmann et al, 1992). The complete nucleotide sequence of several members of the group is already known (Allison et al, 1986;Domier et al, 1986;Robaglia et al, 1989;Lain et al, 1989;Maiss et al, 1989;Teycheney et al, 1989;Johansen et al, 1991 ; * Author for correspondence. Fax +33 1 30 83 31 95. e-mail robaglia@oxygene.versailles.inra.fr Nicolas & Lalibertr, 1992;Yeh et al, 1992;Jayaram et al, 1992;Vance et al, 1992;Thole et al, 1993;Palkovics et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…The complete nucleotide sequence of seven different potyviruses has been documented: tobacco etch virus (TEV) (Allison et al, 1986), tobacco vein mottling virus (TVMV) (Domier et al, 1986), plum pox virus (PPV) (Maiss et al, 1989;La~n et al, 1989), the necrotic strain of potato virus Y (PVY N) (Robaglia et al, 1989), pepper mottle virus (PepMoV) (Vance et al, 1992), turnip mosaic potyvirus (TuMV) (Nicolas & Lalibert& 1992) and pea seed-borne mosaic virus (Johansen et al, 1991). The sequence analysis of potyviruses and in vitro translation studies of potyvirus genomic RNAs have revealed a single open reading frame (ORF) encoding a large polyprotein.…”
mentioning
confidence: 99%
“…A putative AATAA polyadenylation signal has also been noted for TVMV (Domier et al, 1986), but not for the other potyviruses with sequenced T-terminal regions. However, the possible yeast polyadenylation signal, TATGT, has also been noted for TVMV, TEV and PPV 70 to 90 nucleotides upstream of the poly(A) tail (Maiss et al, 1989).…”
mentioning
confidence: 99%
“…Dideoxynucleotide sequencing was performed according to Sanger (1981) using [35S]dCTP and single-stranded DNA was prepared according to Vieira & Messing (1987). Sequence analyses were performed using the DNASIS program (Hitachi Software Engineering) and sequence data from the following potyviruses: watermelon mosaic virus 2 (WMV-2; Yu et al, 1989), tobacco etch virus (TEV; Allison et al, 1985bAllison et al, , 1986, tobacco vein mottling virus (TVMV; Domier et al, 1986), potato virus Y (PVY; Shukla et al, 1986;van der Vlugt et al, 1989), plum pox virus (PPV; Ravelonandro et al, 1988;Maiss et al, 1989) and Johnson grass mosaic virus (JGMV; Gough et al, 1987).…”
mentioning
confidence: 99%